2003
DOI: 10.1177/076737010301800104
|View full text |Cite
|
Sign up to set email alerts
|

L'évolution et l'état de l'art de la recherche internationale sur le parrainage

Abstract: Cette recherche présente l'évolution et l'état de l'art de la recherche sur le parrainage au niveau international. S'appuyant sur un travail antérieur résumant 80 études anglo-saxonnes publiées avant 1996, cette recherche identifie et analyse 153 études supplémentaires (publiées avant 2002) en les divisant en quatre courants de recherche: la nature du parrainage, la gestion du parrainage, la mesure des effets du parrainage et la stratégie de parrainage. L'évolution et les résultats de chaque courant de recherc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
1
17
0
3
Order By: Relevance
“…Several studies have shown that strong prominence leads to better memorisation in the case of placement in movies (Gupta & lord 1998;lehu 2005) and on television (law & Braun 2000). A review of the literature on sponsoring shows that sponsor memorisation increases with the duration of the exposure (Walliser 2003). A similar effect can be expected for placement in songs:…”
Section: Research Hypothesesmentioning
confidence: 76%
See 2 more Smart Citations
“…Several studies have shown that strong prominence leads to better memorisation in the case of placement in movies (Gupta & lord 1998;lehu 2005) and on television (law & Braun 2000). A review of the literature on sponsoring shows that sponsor memorisation increases with the duration of the exposure (Walliser 2003). A similar effect can be expected for placement in songs:…”
Section: Research Hypothesesmentioning
confidence: 76%
“…Some studies (particularly Tripp et al 1994) have shown that the endorsement of several products by the same celebrity reduces the effectiveness of the partnership, in terms of attitude towards both the advertisement and the brand, and also in terms of purchase intention. More generally, it is accepted that the risk of sponsoring is higher when it is associated with people rather than with events (Walliser 2003). This is particularly the case when a brand is associated with a music star.…”
Section: The Effectiveness Of Placements In Songsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les travaux de recherche sur le parrainage sportif se sont accélérés depuis une dizaine d'années sous l'influence notamment de chercheurs européens. Ils s'articulent autour de cinq courants de recherche (Walliser, 2003(Walliser, , 2006(Walliser, , 2010 portant respectivement sur la nature du parrainage, la gestion du parrainage, la stratégie de parrainage, les considérations légales et éthiques du parrainage et la mesure des effets du parrainage. Ce dernier courant, le plus productif en nombre d'études, mesure l'efficacité du parrainage principalement à l'aune de la notoriété et de ses déterminants.…”
Section: Le Parrainage Sportif Et Son Efficacitéunclassified
“…The success of this type of communications operation is often measured by an increase in brand awareness for the sponsors (Herrmann, Walliser and Kacha, 2011a;Lardinoit and Derbaix, 2001;Walliser, 2003). Researchers have therefore examined the factors that encourage unaided and aided recall of the sponsors' brands (e.g., Walliser, 1996).…”
mentioning
confidence: 99%